Ion Channels and Transporters as Therapeutic Agents: From Biomolecules to Supramolecular Medicinal Chemistry - Giacomo Picci; Silvia Marchesan; Claudia Caltagirone (Biomedicines, 2022)
Ion channels and transporters typically consist of biomolecules that play key roles in a large variety of physiological and pathological processes. Traditional therapies include many ion-channel blockers, and some activators, although the exact biochemical pathways and mechanisms that regulate ion homeostasis are yet to be fully elucidated. An emerging area of research with great innovative potential in biomedicine pertains the design and development of synthetic ion channels and transporters, which may provide unexplored therapeutic opportunities. However, most studies in this challenging and multidisciplinary area are still at a fundamental level. In this review, we discuss the progress that has been made over the last five years on ion channels and transporters, touching upon biomolecules and synthetic supramolecules that are relevant to biological use. We conclude with the identification of therapeutic opportunities for future exploration.